Empowering Health Cadres Through Smartphone-Based Educational Applications for Chronic Kidney Disease (CKD) Prevention - Antia, Antia; Kurtanty, Dien; Dewi, Ratna; Suharti, Suharti; Astuti, Nesya Widia; Abidin, Falenia Putri; Kamila, Mutiara Cahya; Wianti, Sri; Wijayanti, Wijayanti (Jurnal Empathy Pengabdian Kepada Masyarakat, 2026)
Background: Chronic kidney disease (CKD) remains a significant public healt issue, especially in communities with limited acces to early detection and prevention services. In Ciangir Village, low health literacy and limited utilization of health cadres contribute to delayed identification of CKD risk. The aim of the initiative is to empower health workers to enhance their knowledge and skills in the prevention of chronic kidney disease through a smartphone-based educational app, thereby supporting public education and the early detection of risk factors. Methods: The implementation methods include program dissemination, health cadre training, application of the Suster Kita application as an educational medium, as well as mentoring and evaluation. The target of this activity was health cadres in Ciangir Village, Legok District, Tangerang Regency, who then provided education to beneficiary households in their area. The activity was evaluated by measuring knowledge levels using pre-tests and post-tests and assessing the cadres' ability to use the application as an educational medium. Results: The total knowledge score increased from 238 (pre-test) to 256 (post-test), indicating an improvement of 18 points. In addition, cadres demonstrated improved ability to deliver structured health education using digital thechnology. Conclusion: Empowering health cadres through smartphone-based applications shows potential as an effective strategy to improve knowledge and support CKD prevention at the community level. However, further evaluation is needed to assess long-term impact.